Long Passing Accuracy Level of IPPKM Football School Players in Kerinci Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the long passing accuracy level of IPPKM Football School players in Kerinci Regency. This descriptive research employed a survey method with test and measurement instruments. The population consisted of 65 IPPKM Football School players in Kerinci Regency, with a purposive sampling technique selecting 20 players aged 17 years. The Bobby Charlton long passing test was used as the research instrument. Data analysis utilized descriptive statistics to categorize performance levels. The findings revealed that the long passing accuracy of IPPKM Football School players in Kerinci Regency showed 8 players (40%) in the good category and 12 players (60%) in the moderate category. No players achieved excellent, poor, or very poor categories. These results indicate that the long passing accuracy level of IPPKM Football School players demonstrates adequate performance that requires further improvement through systematic training programs.